Geographic Distribution and Influencing Factor Analysis of Green Residential Buildings in China - Ke Guo (MDPI AG, 2021)
Green residential buildings (GRBs) are an important part of the concept of green building. Although green buildings are well studied for geographic distribution and influencing factors, GRBs have not been fully explored or widely noted by parties involved in the building sectors. In this paper, we study the geographic distribution and influencing factors of 2134 GRBs that met the Green Building Evaluation Standard and obtained a green building logo in 2008–2016 in China. First, we analyze the geographic distribution and spatial correlation of GRBs with different star ratings at the provincial and municipal levels by natural break-point method and Moran’s index. Second, we study the aggregation degree of medium- and high-star GRBs in each province by development concentration index and define 42 leading cities with more favorable levels of GRB development. Third, we analyze the correlation between the GRBs’ number and 18 influencing factors covering the social economy and real estate market in the 42 leading cities. According to the analysis, this paper shows that (1) there are differences in the geographical distribution characteristics of different star green buildings in China. (2) The differences in geographical distribution and the spatial correlation of GRBs are more obvious in the study of municipal administrative division levels. (3) The local commercial residential building prices and the local residents’ economic and social statuses, education levels, and living standards are significantly positively correlated with the grade of GRBs.